Pengaruh Viral Marketing dan Brand Awareness terhadap Keputusan Pembelian Produk Skincare Ms Glow (Studi Kasus pada Masyarakat Kec. Muara Sabak Timur Kab. Tanjabtim Provinsi Jambi) - Sopini, Pupu; Susanti, Eka (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The aim of the research is to determine viral marketing, brand awareness and purchasing decisions for MS Glow Skincare Products. In discussing this problem the author uses a qualitative descriptive method by looking for information about symptoms, clearly establishing the goals to be achieved, collecting data as material for conducting research. Ms Glow was founded in 2013, founded by two strong women, namely Shandy Purnamasari and Maharani Kemala. The name Ms Glow is said to be an abbreviation of the names Shandy and Maharani Kemala. Ms Glow is also an abbreviation of the brand motto, namely Magic For Skin. The population in this study were users of MS Glow Skincare products. The sample was determined using the judgment sampling method with 100 consumers as respondents regarding viral marketing, brand awareness and purchasing decisions. The hypothesis was tested using the T test and F test. Based on the results of the linear analysis, the equation Y = 5.814 + 0.676 + 1.100 + e was obtained. The value of the F test calculation (X1 and X2) was 149.011 and the R square value was 0.754 or 75.4%, while the remaining 26.6% was influenced by other factors. The conclusion of this research is that viral marketing and brand awareness have a positive and significant influence, both simultaneously and partially, on purchasing decisions.